Evidential Interpretation Of Medicolegal Opinion: Pardgim Shift From Medical To Legal? (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
The criminal justice system provides remedies for offences, as defined by the law  of the land. So far as “offences against human” in India are concerned, the erstwhile  Indian Penal Code (IPC), Criminal Procedure Code (CrPC), and Indian Evidence  Act (IEA)were major laws that witnessed many amendments. The BHARATIYA  NYAYA SANHITA, 2023 (BNS) completely repealed the former IPC last year.  Criminal investigation agencies rely mainly on examination of a person- living  or dead–as the case may be and subsequently report of such examination by the  Registered Medical Practitioner (RMP) / board of experts form a critical base for  further investigations and legal recourse. Once the case is committed for trial,  the opinion of RMP and analysis reports of various samples collected are also of  immense importance for the prosecution side.  The medicolegal opinion by RMP is based on one’s personal knowledge of “Forensic  Medicine & Toxicology” coupled with practical exposure to such cases.  The recent biomedical and legal literature permits one to conclude that the  evidential interpretation of such opinion/s is more legal than that based on medical  science. With due respect to all concerned stakeholders of the Criminal Justice  Delivery System”, an attempt has been made to review the present scenario and  contemplate solutions, if desired.
Keywords: Criminal Justice System; Evidence; Interpretation